2015
DOI: 10.1007/s00464-015-4345-0
|View full text |Cite
|
Sign up to set email alerts
|

Are there differences between right and left colectomies when performed by laparoscopy?

Abstract: In this large cohort of patients undergoing laparoscopic colectomy, LC carried a higher risk than RC of postoperative complications. These findings provide new data on the differences between the two surgeries. Our findings strengthen the notion that right and left colectomies have a different intraoperative and postoperative course and should be analyzed as two separate entities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 20 publications
1
15
1
Order By: Relevance
“…Unfortunately, patients with a history of recurrent or complicated diverticulitis may have loss of tissue planes as a result of acute or chronic inflammatory processes, especially in the pelvis or along the ureter and gonadal vessels. Therefore, laparoscopic colectomy for diverticular disease is more technically demanding and has a higher rate of intraoperative complications than left colectomy for cancer 7 . Moreover, conversion rates to the open approaches of up to 21% have been reported (ranging from 2.2% to 21%) 7,8,20 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, patients with a history of recurrent or complicated diverticulitis may have loss of tissue planes as a result of acute or chronic inflammatory processes, especially in the pelvis or along the ureter and gonadal vessels. Therefore, laparoscopic colectomy for diverticular disease is more technically demanding and has a higher rate of intraoperative complications than left colectomy for cancer 7 . Moreover, conversion rates to the open approaches of up to 21% have been reported (ranging from 2.2% to 21%) 7,8,20 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, laparoscopic colectomy for diverticular disease is more technically demanding and has a higher rate of intraoperative complications than left colectomy for cancer 7 . Moreover, conversion rates to the open approaches of up to 21% have been reported (ranging from 2.2% to 21%) 7,8,20 . Conversion to laparotomy has been reported to be even higher in patients with complicated fistulizing disease, with figures of up to 34.7%, 21 with higher conversion rates being associated with higher complication rates 22 and financial healthcare burden 10 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the type of surgery was not associated with POI ( P = 0.242). Although one retrospective study suggested that right-sided laparoscopic colectomy is associated with a four-fold higher risk of POI than a left-sided laparoscopic colectomy [ 18 ], another study failed to demonstrate a relationship between the risk of POI and the anatomical location of the surgery [ 19 ]. Thus, considering our results together, the impact of the anatomical location of the surgery on the risk of POI may not be substantial.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have discussed the differences between right and left colectomies and have reported inconsistent results for short-term complications. Some studies [ 24 , 25 ] concluded that right colectomies were associated with better outcomes, whereas others [ 26 ] reported that left colectomies were superior. Another study [ 27 ] found no difference in the complication rates when right and left colectomies were compared.…”
Section: Discussionmentioning
confidence: 99%